2007
DOI: 10.4103/1596-3519.55727
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and uptake of cervical cancer screening in Owerri, South-Eastern Nigeria

Abstract: Background: Cancer of the cervix is the most common cancer of the female genital tract and accounts for about two hundred and fifty thousand deaths yearly most of which occur in the developing countries. It has assumed greater prominence with the decrease in deaths due to infective causes and the increase in the incidence of HIV/AIDS which is a predisposing factor. A significant drop in its incidence has been recorded in the developed countries as a result of intensive program of cervical screening. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
94
6

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 12 publications
17
94
6
Order By: Relevance
“…This could also be attributable to the course of study in the university environment. This is at variance with earlier work in which the source of information for cervical cancer screening students was mostly from health professionals [8][9][10].…”
Section: Discussioncontrasting
confidence: 75%
“…This could also be attributable to the course of study in the university environment. This is at variance with earlier work in which the source of information for cervical cancer screening students was mostly from health professionals [8][9][10].…”
Section: Discussioncontrasting
confidence: 75%
“…9 The present study showed that 79% respondents have average knowledge. A study conducted by Awodele O in 2011, had shown that 99% of nurses had good knowledge of cervical cancer which is consistent with the earlier study from South Eastern Nigeria.…”
Section: Discussionsupporting
confidence: 50%
“…The WHO predicts that by the year 2025, 5,000 new cases of cervical cancer and 3,361 cervical cancer deaths will occur annually in Ghana (WHO, 2007). Several studies have shown low levels of knowledge in cervical cancer across different literacy levels in Africa (Ezem, 2007) and awareness of this disease on the continent is very poor yet mortality remains relatively high. Knowledge of cancer patterns in Africa is woefully inadequate, and population-based epidemiological data on the occurrence of cancer in Sub-Saharan Africa especially, are sparse (Okonofua, 2007).…”
Section: Introductionmentioning
confidence: 99%